Emotional and behavioral problems of referred and non-referred children: Analysis of associations with family socio-demographic variables - Kajokienė, Ilona; Žukauskienė, Rita (Psichologija, 2007)
The focus of this paper – analysis of associations of emotional and behavioral problems of referred and non-referred children with family socio-demographic variables. For this purpose, we used data from a clinical sample (N = 780) that consists of children placed for treatment to child psychiatry centers and mental health centers, and data from a representative sample (referred children are excluded) (N = 3191). Worldwide known ASEBA instruments CBCL6/18 and YSR 11/18 were applied in this research to evaluate children’s emotional and behavioral problems, also a questionnaire to collect data on socio-demographic variables about child and his family. We made a comprehensive analysis of social, demographic, economic variables in relation to emotional and behavioral problems assessed by CBCL and YSR, also comparisons between clinical and representative groups were made. Results show that gender was important variable influencing level of internal and external problems both in clinical and representative samples. Age was more important determinant in representative group. Children from incomplete families showed higher levels of emotional and behavioral disturbances (particularly, external). Children from clinical sample from incomplete families more often were receiving in-patient treatment rather than outpatient treatment. Better educational background (especially that of mothers) was important social factor determining lower levels of psychological problems in both clinical and representative samples. Family SES (income per person) negatively correlated with most CBCL and YSR scales scores, although there were no significant relations with Somatic Complaints and Rule Breaking Behavior scales. Prognostic power of socio-economic, demographic variables to predict child behavioral and emotional problems was assessed. In addition, revised norms for CBCL6/18, TRF6/18 and YSR11/18 are enclosed.